Recent Advances in the Role of Arid5a in Immune Diseases and Cancer - Nyati, Kishan Kumar; Kishimoto, Tadamitsu (Frontiers in Immunology, 2022)
AT-rich interactive domain 5a (Arid5a) is a nucleic acid binding protein. In this review, we highlight recent advances in the association of Arid5a with inflammation and human diseases. Arid5a is known as a protein that performs dual functions. In in vitro and in vivo studies, it was found that an inflammation-dependent increase in Arid5a expression mediates both transcriptional and post-transcriptional regulatory effects that are implicated in immune regulation and cellular homeostasis. A series of publications demonstrated that inhibiting Arid5a augmented several processes, such as preventing septic shock, experimental autoimmune encephalomyelitis, acute lung injury, invasion and metastasis, immune evasion, epithelial-to-mesenchymal transition, and the M1-like tumor-associated macrophage (TAM) to M2-like TAM transition. In addition, Arid5a controls adipogenesis and obesity in mice to maintain metabolic homeostasis. Taken together, recent progress indicates that Arid5a exhibits multifaceted, both beneficial and detrimental, roles in health and disease and suggest the relevance of Arid5a as a potential therapeutic target.